La poética afroandina en la narrativa negra del Perú: El caso de Malambo de Lucía Charún-Illescas y Crónica de músicos y diablos de Gregorio Martínez - Juan Manuel Olaya Rocha (2022)
The present investigation analyzes the conformation of the Afro-Andean discourse in two Peruvian novels: Malambo (2001) by Lucía Charún-Illescas and Crónica de músicos y diablos (1991) by Gregorio Martínez Navarro. One of the objectives is to demonstrate that the African heritage in both novels is built from its relationship with symbolic structures of Andean roots. The conceptual tools that guide our interpretation are the categories of “transculturación” (Ortiz and Rama) and “heterogeneidad” (Cornejo Polar). In this line, we identify that the representation of the African heritage in the two novels apropriates certain indigenous cultural elements, which in many cases implies a loss of elements considered native. This process influences the configuration of an Afro-Andean identity, whose essence does not dilute the particularities of each system; on the contrary, it recognizes the differences, values the individual contribution and, therefore, in several cases, it’s not free of internal tensions or conflicts.